Law and man - Hall, George Clifton (My University, 1896)
Introduction: Law is the social tie between men and by its use man is enabled to accomplish more and more. When a law is properly made interpreted and applied for the one great purpose, to make it possible for men to live happier, to live better, and to induce men to care for and help each other it is truly a blessing to humanity. But what shall we say of a law which is made for the sole purpose of aiding self by making one class rule over others, by taking away one man’s just nights and giving special privileges to others? Shall we call it a curse to humanity? In a highly developed society it may truly be called such but in a barbaric society it is not so bad, for there, in one sense it is a benefit because it makes a man’s life a hard one, whence he begins to ponder the questions, “What rights has this king to rule us in this manner?” “Are there laws just?”
Citation: Hall, George Clifton. Law and man. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Law; Social; Men; Humanity; Class; Privileges; Theses; Manuscripts (documents)